Artistas e empreendedores: um estudo sobre o trabalho criativo na economia do imaterial - Melo, Sharine Machado Cabral (2015)
The aim of this thesis is to draw a genealogy of the events which led creation to be considered as an integrated activity of capitalism. The creative act, which had the fine Arts as its leading exponent, had been regarded as a natural or divine gift , an exception to the economic regime based on scarce resources and on the value extracted from physical strength. However, in the last years, utterances of creative economy or cultural economy have been focusing on creation to generate social and economic wealth. This tendency is visible when contemporary capitalism is studied in the context of immaterial labour, which has a tangible dimension (the materiality of art works or the bodies which produced them), but it is centred essentially on cooperation, signs and affects, extending itself throughout the capture of subjectivity and of the power of life itself. The hypothesis is that the artists are to be seen as entrepreneurs: those who invest their own lives in search of wealth. Mainly, two theoretical trends were used: researches on biopolitic, governmentality and neoliberalism, which had been initiated by Foucault and expanded by Rose, Negri, Lazzarato, Hardt, among others; and researches about creative economy and cultural industries, exposed by British researchers, such as Bennett, Oakley and Hesmondhalgh, who were partly influenced by Cultural Studies. In order to specify Latin American issues, Canclini s work was also used. There are references about Art History, these include: Gombrich, Shiner and Danto; Spinoza s philosophy and Peirce s semiotics have also been utilized as groundwork for the discussion. Aesthetic was specially studied from Kant s, Schiller s, Osborne s and Deleuze s works. Finally, quantitative and qualitative researches were done to investigate the daily practise of the artists. In conclusion, there are opportunities for the arts, but it is necessary to prevent the artistic movements to enclose themselves in their own production chain or to invest only on funding, disputing for public attention. There are new ways of labour exploitation, but artistic power resists or adapts itself to political and economic affairs